MTsS Darul Ulum Banda Aceh وتطبيقها لترقية على مهارة القراءة بـ Rolling Ball وسيلة - Fajriah, Fajriah; Kautsara, Zulfina (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
Based on the result of the observation in grade 2 (2) students at MTsS Darul Ulum Banda Aceh, there had some difficulties for the students in reading skiil, the students unable to understand the text well. The aim of this study is to know the effectiveness of the rolling ball media used to increase students’reading skiil. In this study, the researcher applied the pre-experimental method through one group pre -test post –test design. Samples of this research are 22 students in grade 2 (2) students at MTsS Darul Ulum Banda Aceh. To collect the data, the researcher used the test. The result of this research is the using of rolling ball media is effective to increase students’reading skiil in grade 2 (2) students at MTsS Darul Ulum Banda Aceh . Furthermore, it was found that the result of the T-Test is a significance level (2- tailed) 0.00<0.05.